WordPress 101 - The Complete Guide - Oni, Alexander (Packt Publishing, 2020)
Learn how to build your WordPress website from an experienced WordPress developer About This Video Learn how to choose the right web hosting company Configure a wide variety of WordPress plugins Integrate social media functionality into your website Build your own WordPress website or blog Optimize your website to increase its visibility on Google, Bing, and other major search engines Protect your website against hackers and malware In Detail Do you want to learn how to build your own website even if you have no prior experience or programming and coding knowledge? This course will help you get started, whether you're looking to create a WordPress website for personal use or for your business. You'll start with the installation of WordPress. Progressing through the sections, you'll explore how to create a custom webmail account. To build on your skills, you'll even get to grips with configuring various WordPress plugins. In addition to this, the course covers the latest features in the WordPress 5.5 version update that will help you to further enhance your web page. By the end of this course, you'll have gained a comprehensive understanding of WordPress and have learned how to confidently build a WordPress website through expert guidance.